Distinct room-temperature dielectric transition in a perchlorate-based organic–inorganic hybrid perovskite. Issue 48 (17th November 2017) - Sun, Yu-Ling; Shi, Chao; Zhang, Wen
Abstract : Distinct room-temperature dielectric transition is realized in a perchlorate-based organic–inorganic hybrid perovskite with the introduction of a polar cationic guest. Abstract : The organic–inorganic hybrid perovskite (H2 hpz)[K(ClO4 )3 ] (H2 hpz = diprotonated homopiperazine) exhibits a distinct room-temperature dielectric transition. The dielectric switching at 303 K is associated with an order–disorder transition of the polar guest cation confined in the cage, corresponding to a dynamic change between motional and frozen states.